Abordajes. Sobre comunicación y cultura - Said-Hung, Elías Manuel (Methaodos-Revista de ciencias sociales, 2022)
El profesor de Comunicación Audiovisual de la Universidad de Valencia Antonio Méndez Rubio presenta en Abordajes. Sobre cultura y comunicación una compilación de textos, publicados previamente en otros formatos, con temáticas diversas, aunque unidas por la aplicación de una perspectiva crítica de la cultura y unas propuestas emanadas del anarquismo metodológico y político. Se trata de un conjunto breve de ensayos de enorme interés y pertinencia, que sin duda ampliarán el horizonte intelectual de sus lectores.
Approaches. About communication and culture
The Audiovisual Communication professor at the University of Valencia, Antonio Méndez Rubio, presents in Approaches. On culture and communication, a compilation of texts, previously published in other formats, with different themes, although united by applying a critical perspective of culture and some proposals emanating from methodological and political anarchism. The work is a short set of essays of enormous interest and relevance, which will undoubtedly broaden the intellectual horizon of readers.
Keywords: política; sociología; cultura de masas; communication; politics; sociology; mass culture; Emerging